2021
DOI: 10.3892/ol.2021.12877
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene legumain promotes thyroid carcinoma progression via the microRNA‑495/autophagy pathway

Abstract: The pseudogene legumain (LGMN) has been reported to regulate cancer cell biology. However, the role of LGMN in thyroid carcinoma remains unknown. Herein, Cell Counting Kit 8 and Transwell assays were performed to evaluate cellular proliferation and invasion capacity, respectively. In addition, a tube formation assay was performed to assess HUVEC angiogenesis. The results showed that LGMN depletion attenuated cellular proliferation, invasion and tube formation ability, and that LGMN expression was dysregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…From our data, we cannot confirm the subcellular location at which these proteins are cleaved; it is possible that the nuclear/cytoplasmic proteins are cleaved within lysosomes or elsewhere in the cell. Few studies have indicated a positive correlation between legumain and autophagy-related proteins such as ATG3 ( 105 ), and microtubule-associated protein 1A/1B-light chain 3 (LC3) ( 106 ). As such, increased legumain expression may associate with increased autophagic flux ( 107 ) and it may be that these observed “extra-lysosomal” cleavages are in fact mediated by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…From our data, we cannot confirm the subcellular location at which these proteins are cleaved; it is possible that the nuclear/cytoplasmic proteins are cleaved within lysosomes or elsewhere in the cell. Few studies have indicated a positive correlation between legumain and autophagy-related proteins such as ATG3 ( 105 ), and microtubule-associated protein 1A/1B-light chain 3 (LC3) ( 106 ). As such, increased legumain expression may associate with increased autophagic flux ( 107 ) and it may be that these observed “extra-lysosomal” cleavages are in fact mediated by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“… 31 LGMN has been demonstrated to be overexpressed not just in breast, prostate, and liver tumor cells but also in the macrophages that compose the tumor microenvironment. 29 , 32 LGMN may promote the progression of TC through the miR-495/autophagy axis, 33 and VCAM1 can promote the migration and invasion of TC cells. 34 PLEKHA7 contributes to the trafficking and retention of transmembrane proteins, including nectins, Tspan33, and the copper pump ATP7A, at cell-cell junctions and lateral membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-495-3p is a short-stranded RNA blocking post-transcriptional translation of legumain [149] and is proposed as a biomarker in some cancer types. Furthermore, LGMNP1 also promotes thyroid carcinoma progression via the miR-495 and autophagy pathway [150].…”
Section: Role Of Legumain In Cancermentioning
confidence: 99%